Launching your autistic youth to successful adulthood : everthing you need to know about promoting independence and planning for the future - Manassis, Katharina (Jessica Kingsley Publishers, 2020)
"The transition from high school to adulthood is one of the most challenging times for young people with autism spectrum disorder (ASD). What will happen when all their familiar teachers, educational assistants, coaches, and friends disappear after graduation? Who will replace them in the adult world? How will they manage this drastic change? If you are the parent of a youth with ASD and these questions are looming in your mind, this book is focussed on answering all these questions and more. Drawing on her experiences as a mother of a child with ASD and a child psychiatrist, Katharina Manassis shares common transition-related challenges and provides practical solutions for each. It helps parents plan for every stage of the journey. This includes what a successful transition can mean and how to set realistic goals, exploring specific aspects of the transition such as employment, independence and social life, and how to address long-term concerns such as living arrangements and financial support"--